Peer Review : the case of Online Brazilian Journal of Nursing - Isabel CF da Cruz (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
The article discusses some issues relating to peer review in the evaluation of papers submitted to OBJN. It points out the need to promote discussions about scientific divulgation at Nursing Schools.